Investigating the content and structure of post-secondary preparation courses at McMaster University - Choksi, Hani; Li, Megan; Lucchese, Alexandra; Al-Humuzi, Noor; Al-Humuzi, Huda; Gravely, Evan (Prepared by the McMaster Research Shop for McMaster's INSPIRE Office of Flexible Learning, 2023)
University INSPIRE Office of Flexible Learning recognizes that a large gap exists in the skills, knowledge, and expectations of first-year students transitioning from high school to university. As a result, the INSPIRE intersession learning courses were designed to help incoming first-year students transition into their first year of university. McMaster Research Shop collected feedback on the experiences of first and second-year McMaster University students to identify course topics and a structure that would be appropriate for INSPIRE courses.
Keywords: Hamilton, community-engaged research, intersessional learning, students, first year experience